Community Service Training and Mentoring Preparing Simple Financial Reports for MSMEs Cideheng Village, Kemanisan Subdistrict, Serang City - Dini Purnamasari; Novia Hindayani (EQUATOR SINAR AKADEMIA, 2026)
This community service activity was carried out at MSMEs engaged in the buying and selling of large plastic containers and cans in Cideheng Village, Kemanisan Subdistrict, Serang City. This activity was motivated by the still limited ability of business actors in preparing simple financial reports as a basis for business decision-making. The objective of this activity was to improve the knowledge and skills of MSME actors in recording transactions and preparing simple financial reports. The methods used included observation, interviews, training, and direct mentoring in financial recording practices. The results of the activity showed an increase in the understanding and ability of partners in grouping transactions, recording cash flow, and preparing simple financial reports more systematically. Training and mentoring involving the active participation of business actors have proven effective in increasing the financial management capacity of MSMEs and supporting the sustainability of independent businesses.